From Sociology to Computing in Social Networks Theory, Foundations and Applications - Memon, Nasrullah; Alhajj, Reda.; SpringerLink (Online service) (Vienna : Springer Vienna, 2010)
Important aspects of social networking analysis are covered in this work by combining experimental and theoretical research. A specific focus is devoted to emerging trends and the industry needs associated with utilizing data mining techniques. Some of the techniques covered include data mining advances in the discovery and analysis of communities, in the personalization of solitary activities (like searches) and social activities (like discovering potential friends), in the analysis of user behavior in open fora (like conventional sites, blogs and fora) and in commercial platforms (like e-auctions), and in the associated security and privacy-preservation challenges; as well as social network modeling, scalable, customizable social network infrastructure construction, and the identification and discovery of dynamic growth and evolution patterns using machine learning approaches or multi-agent based simulation. These topics will be of interest to practitioners and researchers alike in this dynamic and growing field.
Social Networks: A Powerful Model for Serving a Wide Range of Domains -- Social Networks: A Powerful Model for Serving a Wide Range of Domains -- Mining-based Social Network Methods -- Employing Social Network Construction and Analysis in Web Structure Optimization -- Mining Heterogeneous Social Networks for Egocentric Information Abstraction -- PROG: A Complementary Model to the Social Networks for Mining Forums -- Socio-contextual Network Mining for User Assistance in Web-based Knowledge Gathering Tasks -- Integrating Entropy and Closed Frequent Pattern Mining for Social Network Modelling and Analysis -- Dynamics in Social Network Models -- Visualisation of the Dynamics for Longitudinal Analysis of Computer-mediated Social Networks-concept and Exemplary Cases -- EWAS: Modeling Application for Early Detection of Terrorist Threats -- Complex Dynamics in Information Sharing Networks -- Harnessing Wisdom of the Crowds Dynamics for Time-dependent Reputation and Ranking -- Dynamics in Social Network Models -- Detecting Communities in Social Networks Using Local Information -- Why Do Diffusion Data Not Fit the Logistic Model? A Note on Network Discreteness, Heterogeneity and Anisotropy -- Interlocking Communication -- The Structural Underpinnings of Policy Learning: A Classroom Policy Simulation -- Social Media -- A Journey to the Core of the Blogosphere -- Social Physics of the Blogosphere -- Twitmographics: Learning the Emergent Properties of the Twitter Community -- Dissecting Twitter: A Review on Current Microblogging Research and Lessons from Related Fields -- Software Applications -- Unleash the CSS-Factor -- Extending SQL to Support Privacy Policies -- nCompass Service Oriented Architecture for Tacit Collaboration Services -- SOA Security Aspects in Web-based Architectural Design.
Keywords: Computer science; Social sciences -- Data processing; Computer Science; Computer Appl. in Social and Behavioral Sciences